A Report on the Teaching of Software Ecosystems in Software Engineering Discipline - Coutinho, Emanuel F.; Santos, Italo; Moreira, Leonardo O.; Bezerra, Carla I. M. (Companion Proceedings of the Brazilian Symposium on Software Engineering (SBES); 2019: Companion Proceedings of the 33th Brazilian Symposium on Software Engineering, 2020)
Software Engineering is a crucial discipline present in several undergraduate courses, often due to the incorporation in its curriculum and many times focusing only in technical artifacts analysis, which leads to restricting social and business aspects, and limiting a global vision. Software Ecosystem (SECO) is a collection of software products with some degree of symbiotic relationship, consisting of a set of actors working as a unit interacting with a market distributed between software and services, along with the relationships between these entities. Motivated by the SECO diffusion, the idea of incorporating its teaching in the Software Engineering discipline seems to be attractive. However, a drawback to SECO research is the lack of modeling support. Furthermore, there is a need for more examples of SECO models, mainly close to the students' reality. This work aims to report the teaching of SECO in the Software Engineering discipline. For this, a qualitative analysis of a questionnaire with students' answers was designed. As a result of this work, we concluded that adding the teaching of ECOS in the Software Engineering discipline provides a global view of the systems development, mainly social aspects and evolution.